2016
DOI: 10.1002/jnr.23876
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the epigenetic basis of sex differences in depression

Abstract: Epigenetics refers to potentially heritable processes that can mediate both lasting and transient changes in gene expression in the absence of genome sequence alterations. The field of epigenetics has introduced a novel understanding of the mechanisms through which the environment can shape an individual and potentially its offspring. This review examines the current literature exploring the role of epigenetics in the development of mood disorders such as depression. Depression is ~2-fold more common in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 131 publications
(173 reference statements)
1
31
0
1
Order By: Relevance
“…Regarding the association between depression symptoms and female patients, a study conducted to investigate the association between genetic factors and depression pointed out that women are on average twice as likely as men to have episodes of depression. However, despite the existence of justifications related to genetic, neuro-hormonal and psychobiological aspects, it is believed that due to the lack of data regarding the actual number of patients affected by this clinical diagnosis, investigations about the characteristics of this disease are limited, thereby highlighting the importance of new studies on this prevalence in the present day (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association between depression symptoms and female patients, a study conducted to investigate the association between genetic factors and depression pointed out that women are on average twice as likely as men to have episodes of depression. However, despite the existence of justifications related to genetic, neuro-hormonal and psychobiological aspects, it is believed that due to the lack of data regarding the actual number of patients affected by this clinical diagnosis, investigations about the characteristics of this disease are limited, thereby highlighting the importance of new studies on this prevalence in the present day (23) .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of rodent studies involving behavioral analyses used male rodents, despite a higher prevalence of MDD in women. Future investigations will require the inclusion of both sexes in animal testing (Hodes et al, 2017), but it is interesting to note that in a mouse model of depression during menopause, Miyata et al (2016b) also found that the gene expression alterations induced by ovariectomy were mainly associated with ribosomal and mitochondrial functions in both the medial prefrontal cortex and the blood, strengthening the results we discussed above. We also only addressed the response to antidepressant treatment with a single drug, fluoxetine, while other drugs with different selectivity for neurotransmitters other than serotonin are frequently used in the clinic (Bagot et al, 2017).…”
Section: Discussionmentioning
confidence: 52%
“…Increasing evidence supports a role for epigenetic changes in the pathogenesis of depression, particularly in response to early life stress. The interactions with stress signaling and the pathways for sex differentiation suggest a mechanism by which the activation of stress pathways may act sex‐specifically to control the response to chronic stress . These findings are supported at the gene regulatory level by recent studies on cross talk between SRs and glucocorticoid receptor (GR).…”
Section: Sex Differences and Stress: Intersection At The Level Of Dnamentioning
confidence: 91%
“…Women have twice the lifetime risk of developing depression compared with men and appear to experience symptoms that are more severe and diverse . Like many other major neuropsychiatric conditions, major depressive disorder typically evolves during early adolescence, with an earlier and distinct presentation in girls compared with boys . This suggests that sex‐specific pathways that regulate mood are activated by the onset of puberty and may intersect with stress response pathways to contribute to gender‐specific symptoms …”
Section: Sex Differences and Stress: Intersection At The Level Of Dnamentioning
confidence: 99%